Chromosome translocations and cancer - Mitelman, Felix (Henry Stewart Talks, 2015)
Chromosome translocations, Fusion genes in cancer, Chromosome aberrations in cancer, Clinical significance of findings, Prognostic significance, Imatinib targeted treatment in CML, Survival of CML patients, From discovery to targeted treatment
Reviewed at 2023/09/05